A simple stereoselective synthesis of (+)-[6]-gingerdiol - Kumar, Rathod Aravind; Kashanna, Jajula; Jangili, Paramesh; Das, Biswanath (European Journal of Chemistry, 2013)
A simple stereoselective synthesis of (+)-[6]-gingerdiol has been accomplished starting from vanillin. The synthetic sequence involves Mouroka allylation, diasterioselective iodine induced electrophilic cyclization and ring-opening of an epoxide as the key steps.